KINERJA GURU DITINJAU DARI SUASANA LINGKUNGAN KERJA DI SEKOLAH Yayasan Al-Wathoniyah 4 Jakarta Timur - munzir munzir (Sosio e-Kons, 2011)
Decreasing Performance of teacher it should concern to us all, Decreasing of teacher of courseaffective the quality of the learning process and will ultimately attact the quality of graduates .Increasingly poor performance of teachers may be due to many factors . the purpose of researchto analyze and examine the truth hypothesis about influence the working atmosphere to teacherperformance . the research using survey method the samples taken 30 people.The research instrument using likert scale each 25 question consist of :1 Working atmosphereinstrument 2.Working Instrument. Data analysis using descriptive statistic , simple analysisregresi linier and double regresi linier . Data Analysis done after the formal requirements andclassical assumption violation test result obtained by testing the hypohthesis that atmosphere haspositive working environment significant impact on teacher performance .The result can be used by school to enhance work motivation of teacher to improve theatmosphere of comfortable working environment.Keyword : Teacher, Performance Work Atmosphere